Effectiveness of a multidisciplinary treatment with youth-initiated mentoring for youths with mental health needs from multi-problem families: a quasi-experimental study - Natasha Koper; Yukiko Boin; Hanneke E. Creemers; Levi van Dam; Geert Jan J. M. Stams; Susan Branje (BMC, 2024)
Abstract Background Children from multi-problem families have an increased risk for experiencing mental health problems. These families face problems in several domains that are often found to be chronic and intergenerational. Yet, the effects of mental health care for youths from multi-problem families are small at best, urging research on new treatment programs. The InConnection approach is an integrated care program to improve resilience of youths with mental health needs from multi-problem families by connecting professional expertise from multiple disciplines with the informal social network of the youth. Youths are asked to nominate a youth-initiated mentor (YIM) from the supportive adults in their network. Methods This quasi-experimental study compared the effectiveness of the InConnection approach to treatment as usual in a sample of 107 families (n = 66 intervention group, n = 41 control group) with n = 115 youths receiving treatment (cases). Youths (n = 102 reports, M age = 15.59 years), parents (n = 85 reports) and case managers (n = 107 reports) responded to questionnaires four times over 15 months. Using these data, we measured youth resilience as the primary outcome, seven secondary outcomes, and three intermediate outcomes. Results Latent growth models showed only one significant change in outcomes over time across conditions, namely a decrease in case manager-reported child unsafety, and only two condition effects, which were both parent-reported. Parents in the InConnection group reported improvements over time in youth's emotional and behavioral problems and their own positive parenting, whereas control parents reported no changes (ps ≤ 0.013). Discussion The treatment conditions were not effective in improving most of the youth and parental outcomes over time, except for child safety reported by the case manager. The InConnection approach only outperformed care as usual on two parent-reported outcomes. Future research should examine for whom and under what circumstances the InConnection approach works more convincingly. Trial registration Netherlands Trial Register NL7565. Retrospectively registered on 05/03/2019.